2023
DOI: 10.1021/acs.orglett.3c01329
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Charge-Transfer Complex Enables Hydroarylation of Alkenes for Heterocycle Synthesis

Abstract: Here, we report a photocatalytic charge-transfer complex (CTC) strategy for one electron reduction of alkenes using thiolate as a catalytic electron donor. This catalytic CTC system could engage hydroarylation of both activated and unactivated alkenes for the synthesis of various heterocycles. The reactions do not require any photocatalysts or acids and are easy to perform. Mechanistic studies revealed the formation of a CTC between catalytic thiolate and alkene.Letter pubs.acs.org/OrgLett

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In 2023, He, Tu, and Chen introduced another photocatalytic CTC strategy employing thiolate as the catalytic electron donor for the hydroarylation of both activated and unactivated alkenes, enabling the synthesis of various heterocycles (Scheme 8). [35] In contrast to the earlier work by Yu and others, this reaction employs 20 mol% PhSNa as the catalytic electron donor without the need of additional reductants. Remarkably, this protocol operates under photocatalyst-free conditions, Scheme 6.…”
Section: Reduction Of Alkenes With Ctcmentioning
confidence: 96%
“…In 2023, He, Tu, and Chen introduced another photocatalytic CTC strategy employing thiolate as the catalytic electron donor for the hydroarylation of both activated and unactivated alkenes, enabling the synthesis of various heterocycles (Scheme 8). [35] In contrast to the earlier work by Yu and others, this reaction employs 20 mol% PhSNa as the catalytic electron donor without the need of additional reductants. Remarkably, this protocol operates under photocatalyst-free conditions, Scheme 6.…”
Section: Reduction Of Alkenes With Ctcmentioning
confidence: 96%
“…On the other hand, however, the addition of 1 equiv of K 2 HPO 4 as a Brønsted base under otherwise identical conditions completely inhibited the productive pathway, suggesting that the function of 1c ·H as a Brønsted acid is also crucial for the efficient operation of this catalysis (entry 12). Since the absorption spectrum of a mixture of 1c – and 3a is identical to that of 1c – (Figure S12), intervention of an electron donor–acceptor complex or a Lewis adduct between 1c – and 3a could be ruled out, and hence 1c – would be the only excitable species under the reaction conditions. In addition, Stern–Volmer fluorescence quenching experiments revealed that the singlet state of photoexcited 1c –* can be quenched only by 3a (Figure S13).…”
Section: Resultsmentioning
confidence: 99%
“…Despite significant progress in radical addition-induced cyclization for this transformation, the exploration and development of a photocatalytic single electron reduction mode for the reductive cyclization of acrylamide derivatives remain elusive and little explored due to the low electrophilicity of α,β-unsaturated amides . To overcome this challenge, Chen and co-workers recently reported a photocatalytic charge-transfer complex that enables single electron reduction of α,β-unsaturated amides, serving as a key step for the reductive cyclization of acrylamides using thiolate as a catalytic electron donor (Scheme c) . It is worth noting that only two examples have been reported for the construction of isoquinoline-1,3(2 H ,4 H )-diones in these transformations.…”
Section: Introductionmentioning
confidence: 99%